Interest and Learning Outcomes in Natural Science of Grade IV Students of Singajaya Elementary School - Agustin, Evie; Andriani Kumala Dewi, Ririn; Sugiro, Sugiro; Rasilah, Rasilah (MASI Mandiri Edukasi, 2024)
This research aims to evaluate the effect of the Learning Cycle 5E learning model on the interest and achievement of science learning of grade IV students at Singajaya Elementary School, Indramayu Regency. The research method used was experimental, with 20 students as participants. The research used an experimental method with steps: determining the problem, preparing instruments, determining samples, collecting, analyzing data, and preparing reports. The research results show that the Learning Cycle 5E learning model positively influences the increasing interest and learning achievement of fourth-grade students at Singajaya Elementary School, Krangkeng, Indramayu Regency. The analysis results with SPSS 26 showed an average N-Gain value of 0.61 for increased interest in learning and 0.47 for increased learning achievement. This research recommends applying the 5E Learning Cycle model to increase student interest and learning outcomes.